2022
DOI: 10.1002/tbio.202200006
|View full text |Cite
|
Sign up to set email alerts
|

A chlorin e6 derivative‐mediated photodynamic therapy for patients with cervical and vaginal low‐grade squamous intraepithelial lesions: a retrospective analysis

Abstract: Cervical and vaginal low‐grade squamous intraepithelial lesions (LSIL) are associated with persistent human papillomavirus infections, and require an efficacious non‐invasive treatment such as photodynamic therapy due to anatomical characteristics. In this study, we evaluated the clinical efficacy and safety of a chlorin e6 derivative named STBF‐mediated photodynamic therapy (STBF‐PDT) for patients with cervical and vaginal LSIL. A total of 18 patients received STBF‐PDT for 3 to 6 times and followed up for 6 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…(F) Chlorin e6: Another photosensitizer used in PDT for cervical cancer. 45 It exhibits a high absorption rate in the near-infrared region, enabling deeper tissue penetration compared to other photosensitizers. Chlorin e6 has also demonstrated high selectivity for cancer cells over healthy cells, making it a promising candidate for PDT.…”
Section: Discussionmentioning
confidence: 99%
“…(F) Chlorin e6: Another photosensitizer used in PDT for cervical cancer. 45 It exhibits a high absorption rate in the near-infrared region, enabling deeper tissue penetration compared to other photosensitizers. Chlorin e6 has also demonstrated high selectivity for cancer cells over healthy cells, making it a promising candidate for PDT.…”
Section: Discussionmentioning
confidence: 99%
“…A Ce6-derivative obtained from Spirulina sp. was evaluated as a PS for the treatment of cervical and vaginal low-grade squamous intraepithelial lesions (LSIL), associated with persistent human papillomavirus (HPV) infections [ 148 ]. The results showed that the complete remission rates were 88.89% and the HPV remission rates was 94.44% at a 6-month follow-up.…”
Section: Emerging and Innovative Applicationsmentioning
confidence: 99%
“…The manuscript by Yao et al [6] reports on an oncological clinical study on chlorin e6 derivative mediated PDT treatments on 18 patients with cervical and vaginal low-grade squamous intraepithelial lesions. Very high rates of complete response and HPV remission were observed at the 6-month follow-up, higher than achieved, for example, with ALA-induced PpIX as reported recently [7,8].…”
Section: Translation Of Photodynamic Therapy and Photodiagnostics Int...mentioning
confidence: 99%